1999
DOI: 10.1530/eje.0.1410105
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual outcome at 12 years of age in congenital hypothyroidism

Abstract: Background: The intellectual outcome in children with congenital hypothyroidism detected by neonatal screening is generally good; however, subtle neurological dysfunctions, subnormal IQ, or both, have been reported. Objective: To evaluate the intellectual outcome in 12-year-old patients with congenital hypothyroidism, detected by neonatal screening, in an attempt to identify factors that may affect intellectual development. Methods: The intelligence quotient (IQ) of 40 children with congenital hypothyroidism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 17 publications
2
59
1
2
Order By: Relevance
“…In contrast to our findings, some studies have reported an association between endocrinological parameters throughout childhood and intellectual outcome (10,13) and language performance (11). However, in these studies initial treatment regimen consisted of late and low-dose substitution therapy (10,11,13). This suggests that cerebral injury occurs not only prenatally, but may continue postnatally if initial therapy regimen consists of late and low-dose treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, some studies have reported an association between endocrinological parameters throughout childhood and intellectual outcome (10,13) and language performance (11). However, in these studies initial treatment regimen consisted of late and low-dose substitution therapy (10,11,13). This suggests that cerebral injury occurs not only prenatally, but may continue postnatally if initial therapy regimen consists of late and low-dose treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Children with athyreosis had lower IQ than those with dysgenesis. This is in line with earlier studies (10,13). In addition, among all neonatal variables, only pretreatment T4 levels were associated with outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In children with congenital hypothyroidism who receive substitutive L-T 4 treatment within the first weeks of life, a rapid normalization of TSH levels seems to be associated with a higher intelligence quotient (IQ) later in life. Furthermore, poor compliance to the therapy, documented by increased levels of TSH in the presence of normal levels of thyroid hormone, has been associated with lower intellectual performance and decreased visual-spatial ability (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have indicated that children who receive early treatment for CH have a normal intelligence quotient combined with attention problems (2,3), motor deficits and defects in visuospatial skills, language and memory (4,5). Several studies have correlated these problems with the severity of CH and others with the timing in starting treatment (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%